Individualisation of the Dose of Letrozole for Ovulation Induction in Infertile Women with Polycystic Ovary Syndrome Based on Clinical and Ultrasonography Criteria: A Cohort Study - Pratyasha Peepal; Padmalaya Thakur; Anubhuti Patel; Jyotiranjan Sahoo; Sujata Pradhan; Manisha Sahu (Journal of Human Reproductive Sciences)
Background: Conventionally, letrozole for ovulation induction (OI) in polycystic ovary syndrome (PCOS) is started at a dose of 2.5 mg, which is gradually escalated depending on the follicular response. The minimum dose required for follicular response for a particular patient is yet to be determined. Aim: The aim of the study was to compare various clinical and ultrasonographic characteristics of patients with successful OI with different doses of letrozole and individualise the dose of letrozole. Setting and Design: This prospective cohort study was conducted in a tertiary care teaching hospital from December 2019 to March 2024. Materials and Methods: Ninety-seven patients were treated with a starting dose of 2.5 mg of letrozole. The dose was increased to 5 and 7.5 mg without a follicular response. Various clinical and ultrasonographic characteristics were compared. Statistical Analysis Used: Data entered in Microsoft Excel and analysed using SPSS version 27. P < 0.05 was statistically significant. Results: Of 97 patients, 10 were lost to follow-up. Eighty-one (93.1%) patients had a positive response to letrozole. Six (6.9%) patients did not respond to the maximum dose of 7.5 mg of letrozole. Waist circumference, maximum antral follicle count per ovary and volume of the largest ovary were significantly different for patients who responded to different doses of letrozole (P < 0.05). Further analysis revealed that an ovarian volume of 10 cc or more is a risk factor for non-response to 2.5 mg of letrozole. Conclusion: The ovarian volume can be considered when determining the dose of letrozole in PCOS.